Hypervalent-iodine-mediated oxidation followed by the acetoxylation/tosylation of alpha-substituted benzylamines to obtain alpha-acyloxy/tosyloxy ketones - Rupanawar, Bapurao D.; Mane, Kishor D.; Suryavanshi, Gurunath (New Journal of Chemistry, 2022)
An efficient and metal-free method has been developed for the sequential oxidation of alpha-alkylbenzylamines followed by acetoxylation or tosylation for the synthesis of alpha-acyloxy/tosyloxy ketones using hypervalent iodine(iii). The employment of a simple starting material, broad substrate scope and operational simplicity are the key features of this protocol.